Household air pollution is associated with disease severity in Ugandan children hospitalized with hypoxemic pneumonia - Ayla Ahmed; Sehaj Sandhu; Sophie Namasopo; Juliet Nabwire; Qaasim Mian; Andrea L. Conroy; Jackson Amone; Charles Olaro; Robert O. Opoka; Michael T. Hawkes (PLoS ONE, 2026)
Background Household air pollution (HAP) due to biomass fuel use is a risk factor for childhood pneumonia, a leading cause of under-five mortality globally. This study examined the relationship between HAP and disease severity in Ugandan children hospitalized with hypoxemic pneumonia. Methods We conducted a retrospective case-control study across 20 Ugandan hospitals. PM 2.5 exposure was estimated using caregiver-reported fuel use, cooking duration, kitchen structure, and ventilation. Pneumonia severity was assessed clinically, and associations were analyzed using non-parametric tests. Results We included 735 children (median age 9 months, 42% female) hospitalized with hypoxemic pneumonia. Most households used firewood (84%) or charcoal (16%) for cooking. Other HAP sources included cigarette smoke (17%) and open-flame lighting (17%). The median estimated personal PM 2.5 exposure was 145 µg/m³ (IQR 79–270), and 732 children (99.6%) exceeded the recommended WHO limit of 15 µg/m³. Chronic HAP-related symptoms included cough (57%), red eyes (41%), rhinorrhea (38%), difficulty breathing (22%), and wheeze (6.5%). Higher PM2.5 exposure was significantly associated with more frequent red eyes (p = 0.0073), rhinorrhea (p = 0.016), and difficulty breathing (p < 0.0001). The median SICK score was 3.9 (IQR 3.4–5.0). Higher scores correlated with higher PM 2.5 exposure (τ = 0.15, p < 0.0001) and increased mortality risk (p = 0.0024). Higher PM 2.5 exposure was also linked to WHO danger signs, lower SpO 2 at admission, longer duration of oxygen therapy, and greater total oxygen volume administered over the hospital admission (p < 0.05 for all). Conclusion Household PM 2.5 exposure from biomass combustion is associated with greater pneumonia severity in hospitalized children under five. Reducing household air pollution through cleaner fuels, better ventilation, and behavioral changes may improve outcomes for a leading cause of child mortality globally.